Self-Efficacy Training as a Strategy to Improve Career Maturity of Vocational High School Students - Nur Aisyah; Riswan Riswan; Siti Qomariah; Siti Aisyah Wahyuni (TAUJIHAT: Jurnal Bimbingan Konseling Islam, 2024)
Self-efficacy training is needed to improve the career maturity of vocational high school students to be better prepared to face the demands of the working world. This study aims to test the self-efficacy training module in improving the career maturity of vocational high school students. This study used a quantitative experimental method involving 15 students as research subjects. Sampling used a purposive sampling technique with cluster sampling criteria. This study used a career maturity scale of 34 statement items as the main instrument. The data obtained were analysed using an independent t-test on the IBM SPSS version 21 application. The results of the analysis showed a significant difference in career maturity in the experimental group and the control group after the experimental group was given self-efficacy training (t = -2.742 and sig. = 0.011), meaning that providing self-efficacy training can improve the career maturity of vocational high school students. Suggestions for guidance counsellors and schools can integrate self-efficacy training programs on an ongoing basis to help students develop career maturity. This study provides an overview that increasing self-efficacy through training can be an effective strategy in preparing vocational school students to face the demands of the world of work, so it is worthy of being applied more widely in other vocational schools.